주행 측정 차량을 이용한 국내 자동차 대기오염 연구 동향 - 배귀남; 이승복; 김경환; 곽경환 (한국대기환경학회, 2023)
Vehicle emission is a dominant source of air pollutants in urban areas. For protecting citizen’s health, vehiclerelated air pollution has been continuously monitored at roadside air monitoring stations. Mobile laboratory (ML) with a high spatial resolution has been operated to investigate vehicle-related air pollution on roads in detail since early 2000s. In this work, vehicle-related air pollution studies using an ML carried out by the KIST research team in Korea was extensively reviewed. Studies on on-road monitoring, tunnel measurements, and air pollution map were discussed. International collaborations were also mentioned. Recently, MLs are popularly utilized by many research teams in Korea to characterize spatial air pollution distribution.